Extending the Biopsychosocial Conceptualisation of Chronic Post Surgical Pain in Children and Adolescents: The Family Systems Perspective - Toby Newton-John (Taylor & Francis Group, 2022)
A substantial number of children and adolescents undergoing surgical procedures, as many as 40% in some estimates, will go on to develop chronic post surgical pain (CPSP). Because of the significant negative impact of CPSP on social and emotional milestones, as well as the child's quality of life, it is important to identify modifiable factors that are associated with the onset and maintenance of the condition. Research has demonstrated that parent factors can play a role in pediatric chronic pain, however there has been little examination of parent and family influences on the transition to CPSP. Family systems theories, which consider the influence of the family unit overall on the behaviour of individuals members, have been applied to the eating disorders literature for decades. This narrative review proposes a novel application of family systems theory to pediatric CPSP, and in particular highlights the role that parental dyadic factors may play in the development and maintenance of persistent pain following surgery in children and adolescents.